P.037 Keeping track of time: emphasizing symptom onset-to-hospital time in stroke care. (5th June 2019) - Freedman, DE; Behih, N; Elmeligi, A; Sahlas, D
Abstract : Background: The Canadian Stroke Best Practice Recommendations target a median door-to-needle time of 30 minutes. However, brain tissue becomes damaged with any delay from symptom onset. Efficiencies may be gained prior to hospital arrival, by evaluating the timeliness of patient access to hospital from symptom onset, as well as by improving healthcare provider communication, prior to arrival of the patient.Methods: We engaged with hospital administration, paramedic services, allied health colleagues, physicians, and engineers, to develop Kairos, a secure online platform that healthcare providers can utilize to track progress en route to hospital, as well as to share pertinent stroke patient information, prior to arrival.Results: Kairos is built on React Native, allowing users to access it on android or iOS devices. Paramedics select patient identification, symptom onset time, and associated symptoms. The receiving hospital can add doctors to the patient's thread, and the stroke team can prepare for patient arrival.Conclusions: We plan to measure the median symptom onset-to-hospital time in patients with strokes, and monitor the change in door-to-needle time following implementation at an Ontario Regional Stroke Centre.